Accompaniment for Students’ Entrepreneurial: Independent Entrepreneurial Practice in Palangka Raya City: Pendampingan Kewirausahaan Mahasiswa: Praktik Berdagang Mandiri Area Kota Palangka Raya - Harinie, Luluk Tri; Iswandyah Raysharie, Puput; Sukmani, Meylinda (Universitas Lancang Kuning, 2024)
The purpose of the accompaniment is to support students; entrepreneurial practices through the learning process of entrepreneurial courses in the classroom through Google Meet learning media and business practice in the area outside of the college in Palangka Raya City. The accompanying activities are carried out for six months in the academic year 2023/2024 in the Department of Management, Faculty of Economics and Business, University of Palangka Raya, involving sixty students. The methods of accompanying are discussions, question and answer, and entrepreneurship. The output has successfully aroused the interest of students to start entrepreneurship independently to sell their products creatively. This activity creates entrepreneurial interest among students and is in accordance with MBKM policy in encouraging the development of students' entrepreneurial interests. This clarifies the balance in the process of learning activities carried out in the classroom and outside college.